Classical mechanics a textbook - Chandra, Suresh (Alpha Science International, 2009)
Classical Mechanics begins with the Elementary Principles of Classical Mechanics and introduces the generalised coordinates, Lagrangian formulation and Hamiltonian Formulation and the Central Force used for derivation of Kepler's laws of planetary motion. The topic on Small Oscillations is introduced and applied for a number of systems. Rotational motion for a Rigid-body and High speed (relativistic) motions are discussed under Special Relativity. Finally, the four vectors, four velocity, four momentum etc. are also discussed.